2018
DOI: 10.1299/mej.17-00538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 3D-printing conditions on physical properties of hydrogel objects

Abstract: In this paper, we present the relationship between printing parameters of a 3D gel printer "Soft and Wet Intelligent Matter-Easy Realizer (SWIM-ER)" and mechanical properties of the fabricated gel objects by SWIM-ER. The printer is able to fabricate hydrogel objects by scanning of ultra-violet (UV) light irradiation (photopolymerization). Various hydrogels objects were printed with different scanning velocity of UV light. We measured the water content and mesh sizes of gel objects utilizing Scanning Microscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…The gel electrolyte becomes softer and more stretchable when the scanning velocity increases because of the failure in constructing dense network as a result of inadequate curing time. [ 26 ] As the UV light power increases, the number of crosslinking point increases resulting in densely crosslinked network formation. The reaction time is long in multiple scanning time and low scanning velocity, as a result the GPEs become hard and brittle.…”
Section: Resultsmentioning
confidence: 99%
“…The gel electrolyte becomes softer and more stretchable when the scanning velocity increases because of the failure in constructing dense network as a result of inadequate curing time. [ 26 ] As the UV light power increases, the number of crosslinking point increases resulting in densely crosslinked network formation. The reaction time is long in multiple scanning time and low scanning velocity, as a result the GPEs become hard and brittle.…”
Section: Resultsmentioning
confidence: 99%
“…The UV radical polymerization reaction is commonly used with SWIM‐ER. It has been shown that the total amount of UV light irradiation is an important factor in 3D gel printing . SWIM‐ER is different from other stereolithographic 3D printers in that the number of scans per layer is possible to be specified.…”
Section: Methodsmentioning
confidence: 99%
“…SWIM‐ER can form gels with a scan speed ranging from 0.5 to 100 mm s −1 . The elastic modulus of these gels increases as the accumulated light amount increases . The scanning velocity for the bone STL was set at 7.25 mm s −1 and for the flesh STL it was set at 80.0 mm s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many kinds of biological tissues are low-friction [29]; hence, this technique is beneficial for constructing the artificial living tissues. Furthermore, the properties of artificial cell membranes have been widely studied to clarify the physicochemical mechanisms governing the behaviors of living cell membranes [30][31][32][33][34][35][36][37], and 3D hydrogel printing techniques [24,38] have been developed in the related fields. By utilizing low-friction processing and such previously obtained knowledges and techniques, artificial living tissues composed of cell models and polymer gel ECMs can be developed.…”
Section: Introductionmentioning
confidence: 99%